Analysis of Pulse System Dynamics of Phase Synchronization in Multiple Capture Mode - A. L. Shilina (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a model, a method and an algorithm of the simulation of the pulse system dynamics of phase synchronization in the multiple capture mode. Mathematical description of the devices is based on the method of space and state variables and makes it possible to take into account not only pulse and non-linear characteristics of these systems but also their various operational modes including multiple captures. The mode may operate either as secondary (parasite) or as main (operational) one. Necessity of the latter is caused by the fact that pulse systems using phase control principle are rather often applied at high or super high frequencies when realization of a divider with variable division coefficient which is set in the feedback loop is rather complicated or practically impossible. Multiple capture mode permits significantly to simplify the divider or exclude its application in the system. However designing of pulse systems of phase synchronization in multiple capture mode requires some additional research work and this paper is devoted to such investigations.